Peran Orang Tua Dalam Meningkatkan Minat Belajar Anak - Yuliana Pujiningsih; Alfian Ahmad Kurniawan; Nela Rofisian (Jurnal Teknologi Pendidikan Dan Pembelajaran | E-ISSN : 3026-6629, 2023)
This article discusses the role of parents in increasing children's interest in learning. The purpose of this article is to find out the role of parents in building their children's interest in learning. This article uses qualitative research methods by collecting observation data, interviews and documentation. The first conclusion obtained from the results of this research is the role played by parents (1) Instill a love of learning in children. (2) Divide children's study time. (3) Providing motivation to children. And in interest in learning there are supporting factors, namely (1) children's interest. (2) family. (3) facilities. And the factors inhibiting interest in learning are (1) media availability. (2) lack of parental attention. (3) application of learning discipline.